Improving the benefits and cost of using emerging technologies for sustainable recovery from COVID-19 in manufacturing industries - Nur, S. M. Shafaat Akhter; Salman, Sheak; Habib, A. K. M. Ahasun; Ali, Syed Mithun; AlArjani, Ali; Taqi, Hasin Md. Muhtasim (Frontiers in Environmental Science, 2022)
The ongoing COVID-19 pandemic has manifold disastrous effect on different service and production sectors, and manufacturing industries are no exception. Emerging technologies (ETs) can play a pivotal role in resuscitating these ailing manufacturing industries. However, the cost of implementing ETs is a prime concern, while their benefits are considered insignificant from financial and managerial perspective. Nonetheless, the important attributes that will minimize the cost and harness the advantages of the technology for the recovery of the degraded manufacturing industry are still to be explored. This research, therefore, seeks to examine the critical attributes required for the effective deployment of ETs. At first, a detailed literature review was conducted to identify and sort the attributes influencing the effective use of ETs in the manufacturing industries. After that, Fuzzy-TODIM (an acronym in Portuguese for interactive and multicriteria decision making) was used to rate their importance. Given that ETs are being considered to resuscitate the ailing manufacturing industries, this paper will assist industry professionals in resolving the problems posed by the COVID-19 pandemic.